2023
DOI: 10.1039/d3ra02195e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quenching sheds light on early stages of gold nanoparticle formation

Markus Biegel,
Tobias Schikarski,
Paola Cardenas Lopez
et al.

Abstract: Quenching by glutathione enables visualization of intermediate stages of the gold nanoparticle formation. A T-mixer allows precise control of the particle size distribution via the Reynolds number Re.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This formation mechanism involving a rapid burst of nucleation followed by growth through aggregation has been previously reported by Polte et al for gold nanoparticles synthesized using a similar method, albeit without visual evidence. 61 Biegel et al recently showed that the PSD of their synthesized Au NPs approached a selfsimilar distribution with a geometric standard deviation of 1.32 62 as shown by Lee 63 for processes dominated by Brownian coagulation. The final PSDs of this work approach a constant value of 1.21 for the geometric standard deviation, which is in a similar range but indicates that aggregation is not the only growth mechanism.…”
Section: Microscopic View On the Formation Of Silver− Gold Alloy Nano...mentioning
confidence: 90%
“…This formation mechanism involving a rapid burst of nucleation followed by growth through aggregation has been previously reported by Polte et al for gold nanoparticles synthesized using a similar method, albeit without visual evidence. 61 Biegel et al recently showed that the PSD of their synthesized Au NPs approached a selfsimilar distribution with a geometric standard deviation of 1.32 62 as shown by Lee 63 for processes dominated by Brownian coagulation. The final PSDs of this work approach a constant value of 1.21 for the geometric standard deviation, which is in a similar range but indicates that aggregation is not the only growth mechanism.…”
Section: Microscopic View On the Formation Of Silver− Gold Alloy Nano...mentioning
confidence: 90%